Tropical cattle - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Tropical cattle: origins, breeds and breeding policies by W J A Payne and J Hodges 1997 336pp ISBN 0 632 04048 3 price UKL60.00